The economics of travel and tourism - Bull, Adrian. (Longman, 1995)
Resources in tourism. Tourist types. The economics of tourism damand. Tourism enterprises. Supplying travel and tourism products. Equilibrium in tourism markets. Tourism growth and national economies...